Human trafficking in Slovenia: contemporary issues - Eman, Katja (New forms of human trafficking, 2024)
Slovenia was (and remains) the main human trafficking path on the Balkan route. In Central and Eastern Europe, it has been increasing since the 1980s. Still, the Balkans and its neighbouring countries only became the region of origin, transit and destination of human trafficking in the 1990s, immediately after the end of humanitarian crises and wars in former Yugoslavia. Trafficking of women for prostitution was the most common type. Due to its geographical position, Slovenia is primarily a transit country for human trafficking, albeit it sometimes acts as a country of origin and destination. The types of human trafficking and its purposes have changed: apart from sexual exploitation, currently include forced begging and petty crimes, labour exploitation or forced labour, trafficking in human organs, tissues and cells, child trafficking. These phenomena have also been on the rise in Slovenia. Its victims generally come from Southern and Eastern Europe. This chapter presents various types of human trafficking of the twenty-first century detected in Slovenia and discusses its dangers and consequences in the future. The authors conclude that Slovenia has a well-developed policy and practice of prevention and assistance to victims of human trafficking, where criminal justice agencies work closely with NGOs.